Phytochemical Screening, Cytotoxicity Test, and Antibacterial Activity Test of Wungu Plant Extract (Graptophyllum pictum L. Griff) - Arista, Rini Anggi; Jalloh, Mohammed A.; Insani, Fahma Alifia; Balqis, Putri Azzahara; Larasati, Cindy; Arief, Barieq Farial Putra; Fatriani, Rizka (Tropical Biopharmaca Research Center, IPB University, 2023)
Indonesia boasts a rich array of medicinal herbs, including the wungu (Graptophyllum pictum L. Griff), which is known for its potential as an anticancer and antibacterial agent. Here, we used qualitative phytochemical assays to identify bioactive compounds in various parts of the wungu plant (leaves, stem, and roots) and their efficacy in combating cancer and bacterial infections. The brine shrimp lethality test (BSLT) was used to measure anticancer properties and antibacterial activity against Escherichia coli. We found that the leaves contained flavonoids, triterpenoids, phenols, saponins, and alkaloids, whereas the stem and root contained steroids and alkaloids. Notably, the wungu plant exhibited no toxicity, as shown by the cytotoxicity test, indicating a lack of anticancer potential as all parts showed LC50 values exceeding 1000 ppm. However, the antibacterial assays strikingly showed efficacy against bacteria across all parts of the plants, with varying strengths from weak to strong. This study sheds light on the promising antibacterial properties of the wungu plant and its potential as a therapeutic agent.